Length-weight relationship in three species of silverbellies from Chennai coast - Kizhakudan, Shoba Joe; Reddy, P. Sitarami (Indian Journal of Fisheries, 2012)
Length-weight relationship in three species of silverbellies - Photopectoralis bindus, Secutor insidiator and Gazza minutawas studied based on the data obtained from 742, 862 and 1900 samples of each species respectively, collected during theperiod January 2004 -February 2006. Analysis of covariance revealed no significant difference between males, females andindeterminates in all the three species. The coefficients ‘a’ and ‘b’ of the LW equation were derived as 0.000011989 and3.0515 for P. bindus, 0.00002369 and 2.905 for S. insidiator and 0.00002088 and 2.9228 for G. minuta. Statistical test forisometric growth (H0:b=3) carried out using student’s ‘t’-test on the regression coefficient ‘b’ revealed that the values of bestimated for the three species do not deviate significantly from the isometric value of ‘3’ at 5% level.